Callus induction and determination of antioxidative properties of barringtonia racemosa and barringtonia spicata - Dhiya Dalila Zawawi
Barringtonia racemosa (putat kampung) and Barringtonia spicata (putat nasi) are medicinal plants that are traditionally used to treat itch, chicken pox and sore throat. These trees are grown in the wild and very rarely are they planted on purpose. In order to sustain its existance, enough planting materials are required and in vitro propagation technique ia an option. There were many methods involved but in this study, to initiate a culture was by callus induction. To that, the effects of different types of explants, basal media and plant growth regulators on frequency of callus induction (CI%) were evaluated in B. racemosa and B. spicata. The treatments consisted of 2,4-Dichlorophenoxy-acetic acid (2,4-D) with 6-furfuryl aminopurine (kinetin) in various concentrations. The results showed that leaf and endosperm were better explants than anthers and ovules for both species. B. racemosa callus from the endosperm can be induced on the Murashige and Skoog (1962) medium supplemented with 1.5 mg/L 2,4-D plus 0.5 mg/L kinetin meanwhile with B.spicata endosperm, 100.0 % of CI was obtained from the same basal media with 1.0 mg/L 2, 4-D plus 1.0 mg/L kinetin. In the leaf culture, Murashige and Skoog (1962) supplemented with 2.0 mg/L 2, 4-D gave 90.0% of CI for B. racemosa and 86.67% of CI eith B.spicata. Examination of the anatomical section showed that callus obtained from leaves and endosperms for both species were derived from the mesophyll spongy cells and parenchyma cells, respectively. Since the young shoot was edible and had medicinal value, a study was also carried out to detemine the antioxidant properties and total phenolic compounds. The young leaf was divided into five stages with stage one was the first leaf from the shoot tip followed by second leaf until the fifth leaf that were extracted with methanol and chloroform. The highest total phenolic compounds (TPC) was observed in the methanolic extracts of stage one leaf of B. racemosa (0.34 mg GAE/g DW) and B. spicata (0.19 mg GAE/g DW). In the choloroform extracts, the highest TPC were found in stage 5 leaf of B. racemosa (0.018 mg GAE/g DW) and B. spicata (0.023 mg GAE/g DW). Using 1, 1-diphenyl-2-picrylhydrazyl (DPPH) assay, the free radical scavenging ability was evaluated. The highest antioxidant activity was found in methanolic extracts of stage 3 leaf of B. racemosa with IC50 at 33.33 ug/ml. In B. spicata, methanolic extraction of stage 4 leaf gave highest activity at 42.33 ug/ml as compared to the choloroform extraction that gave below 20% activity. The capacity of extracts to inhibit lipid peroxidation was determined by ferric thiocyanate (FTC) and thiobarbituric (TBA) assay where all the extracts showed antioxidants activity with the value above 88%. Generally, methanol extract showed activity in all antioxidant assays applied and choloroform extract only showed in FTC and TBA assay. This study showed the induction of callus growth of B. racemosa and B. spicata were suitable from the leaf and endosperm explants on Murashige and Skoog (1962) that contained 2, 4-D and kinetin. Leaves of both species contained antioxidant compounds when assayed for free radical scavengers and lipid oeroxidation inhibition.